2000
DOI: 10.1063/1.126318
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen on the activation of p-type GaN

Abstract: The presence of oxygen in the annealing environment can exhibit a strong influence on the activation of p-GaN, as demonstrated by experiments described in this letter. We activated p-GaN at 600–900 °C in four environments: ultrahigh purity (UHP) N2 gettered to remove residual O2, UHP N2 without gettering, 99.5% UHP N2/0.5% UHP O2, and 90% UHP N2/10% UHP O2. The resistivity of the p-GaN was lowest when O2 was intentionally introduced during activation and was highest when extra care was taken to getter residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 6 publications
4
54
0
Order By: Relevance
“…Recently, many reports have shown that annealing in N 2 /O 2 gas mixtures [10][11][12] or in air [13] increased hole concentrations significantly even at low temperatures (<600 °C). These results suggest that oxygen plays an important role in breaking the Mg-H complex at relatively low temperatures, however the role of oxygen in this process is not yet understood.…”
mentioning
confidence: 99%
“…Recently, many reports have shown that annealing in N 2 /O 2 gas mixtures [10][11][12] or in air [13] increased hole concentrations significantly even at low temperatures (<600 °C). These results suggest that oxygen plays an important role in breaking the Mg-H complex at relatively low temperatures, however the role of oxygen in this process is not yet understood.…”
mentioning
confidence: 99%
“…The structures differ in the stacking order of the close packed diatomic planes [ Figure 2.1]. The wurtzite structure has a stacking order of AaBbAa… along the [0001] while the zincblende structure has a stacking order of AaBbCcAa… along the [111]. A, B, C (a, b, c) denote the cation (anion) atoms.…”
Section: Crystal Structurementioning
confidence: 99%
“…H is always present in MOCVD growth as it is used as the H 2 carrier gas and in the precursors (TMA, TMG, NH 3 ). Annealing in N 2 or O 2 ambient was found to be an effective method to reduce the H by out-diffusion and to activate the Mg acceptors and achieve p-type conductive GaN and AlN [97,111].…”
Section: Mg Doping Of Alganmentioning
confidence: 99%
“…Waki et al reported that a thin Ni metal is permeable and absorbs hydrogen liberated from pGaN [3]; consequently deposition of a Ni layer might enhance the removal of hydrogen from p-GaN. Hull et al showed further that annealing p-GaN with a metal layer in an environment of O 2 facilitated removal of residual hydrogen via formation and desorption of H 2 O [6]. On the basis of previous work, an efficient method of extracting hydrogen from p-GaN was proposed to be performed without thermal damage.…”
Section: Introductionmentioning
confidence: 96%